Power to the people - Manuel Echavarria::::::photographer:::
UFW organizer and photographer, Manuel Echavarria (second from right) takes a break with UFW supporters in the UFW Office in Santa Maria. The office became a staging ground for boycotts and local strikes. A poster of Bobby Kennedy, an advocate for farm workers, hangs above his head. Manuel Echavarria, segundo de derecha a izquierda, fundador y organizador de la UFW, descansa acompañado de otros partidarios de la UFW en una oficina de este organismo en Santa Maria. La oficina funcionó como escenario para los boycoteos y huelgas locales. Un cartel de Bobby Kennedy, quién apoyaba a los trabajadores agrícolas, cuelga en la pared detras de Echavarria.